Peningkatan Pengetahuan dan Keterampilan Kelompok Tani dalam Pembuatan Pupuk Kompos dari Batang dan Kulit Pisang sebagai Alternatif Pupuk Kimia Mahal - Yoyon Riono; Muhammad Arpah; Marlina Marlina; Nursida Nursida; Intan Sari (Abdi Techno, 2026)
The high cost of chemical fertilizers often hinders optimal agricultural production. The solution lies in organic compost fertilizers made from local materials such as banana stems and peels. However, the farmer group partners have not yet mastered its production. This PKM aims to enhance the knowledge and skills of farmer groups in making compost from banana stems and peels. The method used involves training and mentoring through stages: discussion, site preparation, tools and materials, implementation of extension activities and practice, and monitoring. The results show that partners exhibited very good responses and participation, and felt that their knowledge and skills in producing such compost had increased.